Mechanism of Improving the Innovative Activity of The Insurance Services Market in Uzbekistan - Khamraev Mekhroj Sirojkhonovich (International Journal on Economics, Finance and Sustainable Development, 2021)
The article is devoted to the issues of innovative development of the insurance services market, which is based on the need and importance of creating innovations in the industry. Barriers to the introduction of innovations have also been identified and appropriate ways for their elimination have been identified.